Coordination of Single-Phase Rooftop PVs in Unbalanced Three-phase Residential Feeders for Voltage Profiles Improvement - Safitri, Nelly (Curtin University, 2015)
Three new algorithms are proposed to regulate network voltages and reduce voltage unbalance factor of distribution systems with high penetrations of singlephase rooftop PVs based on the concept of droop control. The first two algorithms rely on reactive power exchange and active power curtailment of rooftop PVs while the third algorithm takes advantage of both reactive power exchange and active power curtailment. Performance of last algorithm under a Monte Carlo-based stochastic framework is also investigated.